Improving adherence to immunosuppression after liver or kidney transplantation in individuals with impairments in personality functioning – A randomized controlled single center feasibility study - Wagner-Skacel, Jolana; Fink, Nadja; Kahn, Judith; Dalkner, Nina; Jauk, Emanuel; Bengesser, Susanne; Mairinger, Marco; Schüssler, Gerhard; Pieh, Christoph; Stadlbauer, Vanessa; Kirsch, Alexander H.; Zitta, Sabine; et al. (Frontiers in Psychology, 2023)
Introduction: Although adherence to immunosuppressive medication is the key factor for long-term graft survival today, 20-70% of transplant recipients are non-adherent to their immunosuppressive medication. Objective: A prospective, randomized, controlled single-center feasibility study was designed to evaluate the impact of a step guided multicomponent interprofessional intervention program for patients after kidney or liver transplantation on adherence to their immunosuppressive medication in daily clinical practice. Methods: The intervention consisted of group therapy and daily training as well as individual sessions in a step guided approach. The primary endpoint of study was adherence to immunosuppression as assessed with the “Basel Assessment of Adherence to Immunosuppressive Medications Scale” (BAASIS). The coefficient of variation (CV%) of Tacrolimus (TAC) through levels and the level of personality functioning was a secondary endpoint. We conducted six monthly follow-up visits. Results: Forty-one age-and sex-matched patients (19 females, 58.5 (SD = 10.56) years old, 22 kidney- and 19 liver transplantation) were randomized to the intervention- (N = 21) or control-group (N = 20). No differences between intervention- and control groups were found in the primary endpoint adherence and CV% of TAC. However, in further exploratory analyses, we observed that individuals with higher impairments in personality functioning showed higher CV% of TAC in the controls. The intervention might compensate personality-related susceptibility to poor adherence as evident in CV% of TAC. Discussion: The results of the feasibility study showed that this intervention program was highly accepted in the clinical setting. The Intervention group could compensate higher CV% of TAC after liver or kidney transplantation in individuals with lower levels of personality functioning and non-adherence. Trial registration: ClinicalTrials.gov, NCT04207125. Registered on 20 November 2019.